Gender Politics in the Lobbying Profession. Issue 3 (September 2020) - LaPira, Timothy M.; Marchetti, Kathleen; Thomas, Herschel F.
Abstract: Although political scientists have increasingly focused on the role of gender in the policy process and the characteristics of individual lobbyists, little is known about the gender politics of the government relations profession. We extend the study of professional women to the unique political context of Washington, DC, lobbying, an important form of political participation that is understudied in terms of gender. Using data from more than 25, 000 individuals registered to lobby the federal government from 2008 to 2015, we show that women account for 37% of the lobbyist population in Washington, that female lobbyists are more likely to work as in-house employees than for contract lobbying firms, and that the largest Washington lobbying firms are strongly biased towards employing men. We add to these findings qualitative data from in-depth interviews with 23 lobbyists to reveal how the professional experiences of women often depend on the idiosyncrasies of lobbying employment and the political nature of their work. We conclude that the underrepresentation of women in the professional lobbying community is an underappreciated problem with broader implications for gender equality in elite political participation.